Penyatuan Regulasi Pembuatan Badan Usaha Dengan Konsep Omnibus Law Serta Peran Notaris di Dalamnya - Anindita, Shafira Rahmania; Rudy, Dewa Gde (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 03 (2022)DO - 10.24843/AC.2022.v07.i03.p10, 2022)
The purpose of this study is to find out whether the idea of the Omnibus Law can integrate regulations for the formation of business entities into one law and to find out the role of a Notary in supporting this attampt. This research use normative legal methods with library research. The results show that attampt to combine regulations into one law with the concept of the Omnibus Law can be carried out, because all forms of business entities have characteristics that can be categorized into various groups.The role of the Notary in supporting  also attampt to use the Omnibus Law concept by making Authentic Deeds that have legal force and can be accountable.